PENGGUNAAN METODE TOPSIS DALAM SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JENIS USAHA WISATA DI LABUHAN BATU - Simamora, Rikardo Lasroha; Munthe, Ibnu Rasyid; Sihombing, Volvo (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
The development of the tourism sector is an important focus in driving local economic growth. In this context, choosing the right type of tourism business is a strategic step in maximizing regional potential. This study aims to investigate the use of the TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) Method in the development of a Decision Support System (DSS) for selecting types of tourism businesses in Labuhan Batu. The initial stage of the research involved analyzing the criteria for selecting the type of tourism business which included aspects of market potential, sustainability, social impact, and infrastructure. The ranking results provide a guide in selecting the type of tourism business that has the highest potential to develop in Labuhan Batu. Sensitivity analysis of changes in criteria weight provides further insight into the effect of weight on alternative rankings. The use of computer technology in this study allows the development of an interactive Decision Support System capable of providing recommendations based on the results of TOPSIS calculations. The conclusion from this study is that the TOPSIS method can be an effective tool in assisting decision makers in choosing the type of tourism business that is in accordance with the characteristics of the Labuhan Batu area.